AB1051 Brucellosis in rheumatology: a study of 27 cases in tunisia. (12th June 2018) - Saadaoui, K.; Sahli, H.; Rekik, S.; Ajlani, H.; Mariem, M.; Aissaoui, T.; Boussaid, S.; Cheour, E.; Elleuch, M.
Abstract : Background: Brucellosis is an endemic zoonosis in the Mediterranean basin. The osteo articular localization, although rare, remains redoubtable. Objectives: The aim of our work is to study the characteristics of osteoarticular brucellosis in Tunisia. Methods: This is a descriptive retrospective study including 27 cases of osteoarticular brucellosis, collected in a rheumatology department over a period of 12 years (2006–2017) Results: The Sex Ratio Female/male was 1.07 with an average age of 50.9 years. 15–76 Diagnosis delay was 5.9 months [0.3–13]. The diagnosis of spondylodiscitis was retained in 23 patients (85.2%) and sacroiliitis in 4 cases (14.8%). Spinal or sacroiliac pain was found in all patients. Fever was present in 22 patients, sweat in 11 patients, loss of weight or appetite were respectively found in 16 and 12 patients. Eleven patient reported fatigue. Laboratory examination found high erythrocyte sedimentation rate in 23 patients with an average of 69.4 mm. 10–120 CRP was elevated in 26 patients with an average of 59.6 mg/L [3.3–237], the WBC average was 9451 elements/ml [5550–14 000]. Wright serology was positive in all cases, Rose Bengal was positive in 15 cases, and IFI was positive in 3 cases. Brucella melitensis was isolated in blood cultures in 3 cases. Standard X Rays showed disk involvement in 21 patients, vertebral lesions in 20 cases and sacroiliitis in 4 patients. Sectional imaging (MRI or CT) was performed for all patients confirming standard X rays data and showing abscess in 13 patients and epiduritis in 7 patients. The most affected spinal segment was the lumbar one (13 cases), cervical localization was found in 5 cases and thoracic in only 1 case. The spondylitis was multifocal in 2 cases. Spinal disc biopsy was performed in only 4 cases, neither anatomopathologic nor bacteriological examination were conclusive. The treatment was based on the cycline and rifampicin combination for an average duration of 4.5 months. 3–9 The evolution was favourable in the majority of the cases with a relapse in only 2 cases. Conclusions: Osteoarticular brucellosis is a focal form of brucellosis, the most frequent location is spinal and whose adequate treatment allows a favourable evolution. Disclosure of Interest: None declared